2012
DOI: 10.1097/ico.0b013e31824afd6c
|View full text |Cite
|
Sign up to set email alerts
|

Open Clinical Study of Eye Drops Containing the Fibronectin-Derived Peptide PHSRN for Treatment of Persistent Corneal Epithelial Defects

Abstract: Eye drops containing the fibronectin-derived PHSRN peptide are clinically efficacious for the treatment of PEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Taking advantage of the improved mechanical stability of the RHCIII-MPC hydrogel, we printed and analysed micropatterns that used human fibronectin (FN) as ''ink''. FN is a cell-interactive protein in the ECM that promotes adhesion and migration of corneal epithelial cells during wound healing [21,22] and has been successfully tested therapeutically for the repair of persistent epithelial defects in human corneas [23]. We quantitatively evaluated the effect of the printed FN micropatterns on the growth of human corneal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the improved mechanical stability of the RHCIII-MPC hydrogel, we printed and analysed micropatterns that used human fibronectin (FN) as ''ink''. FN is a cell-interactive protein in the ECM that promotes adhesion and migration of corneal epithelial cells during wound healing [21,22] and has been successfully tested therapeutically for the repair of persistent epithelial defects in human corneas [23]. We quantitatively evaluated the effect of the printed FN micropatterns on the growth of human corneal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that FGLM-NH 2 + SSSR eyedrops [17] and PHSRN eyedrops [18] facilitated corneal epithelial migration in a rat model of diabetes. Furthermore, both types of eyedrops promoted corneal epithelial wound closure in patients with PEDs [12, 19, 20]. However, treatment of PEDs in diabetic patients with such peptide eyedrops is likely to be insufficient in the presence of other abnormalities of the cornea that impede epithelial migration in response to such drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have previously shown that eyedrops containing the substance P-derived peptide FGLM-NH 2 plus IGF-1 [17] or PHSRN [18] facilitated corneal epithelial wound closure in diabetic rats. In addition to the effectiveness of PHSRN eyedrops for the treatment of PEDs in patients with diabetic keratopathy [12], we also found that eyedrops containing FGLM-NH 2 and either IGF-1 [19] or the IGF-1-derived peptide SSSR [20] were effective for the treatment of PEDs in patients with neurotrophic keratopathy. Despite the potential of these various peptides for the treatment of PEDs associated with diabetic keratopathy, however, we encountered some cases that responded with incomplete epithelial resurfacing.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations